Texture effects due to asymmetric rolling of polycrystalline copper. (15th October 2017) - Uniwersał, A.; Wroński, M.; Wróbel, M.; Wierzbanowski, K.; Baczmański, A.
Abstract: Texture modifications of polycrystalline copper, caused by asymmetric rolling, were studied experimentally and theoretically analysed. Orientation distribution functions and its intensity along the skeleton lines were examined. It was found that texture components after asymmetric rolling are rotated, approximately around transverse direction, as compared with those after symmetric rolling. The rotation angles were determined for characteristic texture components as a function of the rolling asymmetry ratio. Texture heterogeneity across the rolled sheet thickness was also studied. Theoretical predictions of rolling textures were done using two crystalline deformation models. The orientation distribution functions, rotations of texture components and their variation across the sample thickness were determined and compared with theoretical results. Also the stability of final orientations after asymmetric rolling texture was tested. Graphical abstract: Image